79.7k views
2 votes
Solve the system by the substitution method.

X-2y=6
Y=2x-21

2 Answers

4 votes

Answer:


\boxed{x=12, y=3}

Explanation:


x-2y=6\\y=2x-21

Plug y as 2x-21 in the first equation.


x-2(2x-21)=6\\x-4x+42=6\\-3x+42=6\\-3x=-36\\x=12

Plug x as 12 in the second equation.


y=2(12)-21\\y=24-21\\y=3

User Jamesfm
by
5.1k points
5 votes

Answer:

Hey there!

We have two equations, x-2y=6, and y=2x-21.

Thus, we can substitute all y's in the first equation for 2x-21.

x-2(2x-21)=6

x-4x+42=6

-3x+42=6

-3x=-36

3x=36

x=12

y=2(12)-21

y=24-21

y=3

x=12, and y=3.

Hope this helps :)

User Han Zhao
by
5.8k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.